HUBUNGAN PENGEMBANGAN SUMBER DAYA MANUSIA (SDM) DENGAN KINERJA PEGAWAI DI RSUD OTANAHA KOTA GORONTALO - Robbiyatul Al Adwiyah Salihi; Mohamad Ichsan Arifin Antu; Rismunandar Katili (MOTORIK Jurnal Ilmu Kesehatan, 2026)
Human resource development (HRD) is a critical aspect in improving the quality of health services, particularly in hospitals which serve as the frontline of public service delivery. This study aims to analyze the relationship between HRD comprising knowledge, training, and work motivation and employee performance at Otanaha Regional General Hospital (RSUD Otanaha) in Gorontalo City. This research employed a quantitative method with a cross-sectional approach. The sampling technique used was accidental sampling, and the sample size was determined using the Slovin formula, resulting in 138 respondents. Data were collected through a Likert-scale questionnaire and analyzed using the Spearman Rank correlation test. The results showed a significant relationship between knowledge and employee performance (p = 0.000, correlation coefficient = 0.541), as well as between work motivation and performance (p = 0.000, correlation coefficient = 0.404). However, training did not show a significant relationship with employee performance (p = 0.152, correlation coefficient = 0.074). These findings suggest that higher levels of knowledge and motivation lead to better performance, while the existing training programs have not contributed meaningfully to performance improvement. The study concludes that HRD efforts focused on enhancing knowledge and motivation are significantly associated with improved employee performance. Therefore, hospitals are encouraged to prioritize these two aspects and evaluate the effectiveness of their existing training programs.